The usefulness and utilization of Gold-finger retractor for endoscopic thyroid surgery - Ruan, Jian; Dai, Bin; Zhao, Jian Guo; Tao, Long; He, Fan (Frontiers in Endocrinology, 2023)
Aims In endoscopic surgery, the visual field is frequently obstructed by muscles, blood, and even smoke. To overcome this problem, we have developed a new detachable Gold-finger retractor for narrow-space surgery. Methods Gold-finger retractor was used in 30 patients to facilitate surgical field exposure and smoke discharge, while in 27 patients, percutaneous silk thread suspension was employed for the same purpose. Both groups underwent endoscopic unilateral thyroidectomy and unilateral central lymph node dissection via oral vestibular microincision combined with the axillary-assisted approach. A comparative analysis was conducted to evaluate the efficacy of the Gold-finger retractor and silk thread suspension in relation to intraoperative exposure effect, surgical fluency, surgeon’s comfort, operation time, postoperative complications, and length of hospital stay. This analysis was based on surgical video recordings and postoperative indicators. Results With Gold-finger retractor support, surgeons were able to perform meticulous operations. Complication rates were similar between the two groups, and no serious complications occurred. The number of lymph nodes dissected in the Gold-finger group was significantly greater than that in the routine group (12.43 ± 6.18 and 5.7 ± 2.95, respectively). Further analysis of surgeons’ comfort (visibility and convenience in peeling) revealed that the Gold-finger group was significantly better. Electrosurgery smoke was removed effectively with Gold-finger, and the operation time was significantly reduced. Conclusion In thyroid surgery, Gold-fingers enhance visual field resolution, avoid muscle cutting, save time, and improve the surgical experience.